Farmers' perception of climate change and climate-smart agriculture in northern Benin, west Africa - Moutouama, F.T.; Tepa-Yotto, G.; Agboton, C.; Gbaguidi, B.; Sekabira, H.; Tamò, Manuele (MDPI, 2022)
Climate-Smart Agriculture (CSA) is an approach that identifies actions needed to transform and reorganize agricultural systems to effectively support agricultural development and ensure food security in the face of climate change. In this study, we assessed farmers’ perception of climate change, available CSA practices (CSAP) and the determinants of CSAP adoption in northern Benin. A list of CSAP was generated from a workshop with different stakeholders. Face-to-face interviews were then carried out with 368 farmers selected based on stratified random sampling in the study area. Binomial generalized mixed-effect models were run to analyze the relation between socio-demographic characteristics and the use of CSAP. CSAP were evaluated using a three-point Likert scale and the frequency of agreement with the statement that the selected practices meet the pillars of CSA. More than 60% of farmers had heard about climate change, and more than 80% had observed changes in temperature, rainfall amounts and distribution. Thirty-one CSAP were identified in the area, and only 11 were known by more than 50% of farmers. Out of the 12 selected CSAP for the assessment of adoption and evaluation, seven (7) were used by more than 50% of those who knew them. Farmers agreed with the statements that the evaluated practices improved farm productivity and adaptation to climate change but did not mitigate climate change. Ethnic group and education level were the two major factors that significantly determined the use of the evaluated CSAP.